Question
\( g(a)=a^{2}-4 \) \( h(a)=4 a-3 \) Find \( (g+h)(a) \)
Ask by Peters George. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( (g + h)(a) = a^2 + 4a - 7 \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Extra Insights
To find \( (g+h)(a) \), we start by adding the two functions \( g(a) \) and \( h(a) \). Given: \[ g(a) = a^{2} - 4 \] \[ h(a) = 4a - 3 \] Now, we calculate \( (g + h)(a) \): \[ (g + h)(a) = g(a) + h(a) = (a^{2} - 4) + (4a - 3) \] Combining the terms, we have: \[ (g + h)(a) = a^{2} + 4a - 4 - 3 = a^{2} + 4a - 7 \] Thus, \( (g + h)(a) = a^{2} + 4a - 7 \).